Role of Yoga in the Management of Stress - Swain, Dinesh Prasad; Kotsombat, Samran (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Stress has emerged as a very critical life style physical disorder. An unprecedented progress in science and technology has brought about a complete revolution in the economic social and political scenario all over the world. Economic upswing and unlimited opportunities have made man highly ambitious, success oriented and pleasure loving. In desperation of achieving a higher standard of living and fulfilling his ever expanding desires he tries to earn more and more by means, fair and foul. Thus, he is subjected to various stressful situations in life. In modern style of living stress has brought under its grip all categories of people whether he is a school or college student, businessman and an executive a film actor or a player. Thus, it is very clear that we can’t eliminate stress but we can reduce it.